CODESRIA Bulletin Online, No. 8, March 2022 - The Life of a Great Marxist: Aijaz Ahmad (1941–2022)* - Prashad, Vijay (CODESRIA Bulletin, 2022)
Aijaz Ahmad (1941–2022) died at home on 9 March, surrounded by his books and papers and by the warmth of his children and friends Aijaz Ahmad was born in Muzaffarnagar, in British India. He read extensively from an early age and allowed his mind to drift out of the qasba of his childhood. His father shared some radical books with him, which helped him to understand the world outside the Doab region of the Indo-Gangetic Plain and the world beyond the confines of the capitalist system. From an early age, Aijaz began to dream of internationalism and socialism. He studied in Lahore, Pakistan, to which his family had migrated after Partition in 1947–48, but these studies took place as much in college classrooms as they did in cafés and the cells of political organisations. In the cafés, Aijaz met the finest minds of Urdu literature, who schooled him in both lyric and politics; in the political cells he encountered the depth of Marxism, a boundless view of the world that gripped him for the rest of his life. Fully immersed in the leftist political unrest in Pakistan, Aijaz came to the attention of the authorities, which is why he skipped the country for New York. The two passions of Aijaz Ahmad — poetry and politics — flowered in New York. He took his immense love for Urdu poetry to the most renowned poets of his time (such as Adrienne Rich, William Stafford and W.S. Merwin), reciting Ghalib to them, pouring them wine, watching them recover from Ghalib’s language and Aijaz’s explanation of the meaning of the poems. This innovative work resulted in Aijaz’s first book, Ghazals of Ghalib (1971). At the same time, he was involved with Feroz Ahmed with whom he produced Pakistan Forum, a hard-hitting journal that documented the atrocities in South Asia, with a special focus on the military dictatorship of Yahya Khan (1969–1971) as well as the civilian possibilities of Zulfiqar Ali Bhutto (1971–1977); on Pakistan, Aijaz mainly wrote about the insurgencies in East Pakistan (which became Bangladesh in 1972) and Balochistan. It was in this period that he began to write about South Asian politics for such socialist journals as Monthly Review, with which he collaborated for the next several decades. In the 1980s, Aijaz Ahmad returned to India, taking up residence in Delhi and teaching at various colleges in the city (including at Jawaharlal Nehru University). He settled into a rhythm of critique that produced substantial work on three different areas of inquiry: postmodernism and postcolonialism, Hindutva and liberalisation, and the new world order centred around the United States and US-driven globalisation. Based on his great appreciation for culture and literature, Aijaz developed a powerful analysis of the casual way in which the cultures of the Third World were being assessed by metropolitan universities. This work widened outwards to include a strongly negative assessment of postmodernism and postcolonialism, informed by the work of the leading Marxist literary critic, Fred Jameson, and the main critic of Orientalism, Edward Said. At the heart of Aijaz’s criticism of postmodernism and postcolonialism was their disavowal of Marxism. ‘Post-Marxism’, he told me, ‘is nothing other than pre-Marxism, a return to the idealism that Marx went beyond’. For this comment, Aijaz had in mind the highly influential book by Ernesto Laclau and Chantal Mouffe, Hegemony and Socialist Strategy (1985), which viewed the Italian communist Antonio Gramsci as a postmodern thinker. It is in this context that Aijaz began studying Gramsci’s work. Aijaz’s critiques were published in his classic book, In Theory: Classes, Nations, Literatures (Verso and Oxford University press, 1992). It is difficult to describe in a few sentences the impact this work had on scholars across the world. When Marxism was under attack, Aijaz was one of the few thinkers who produced a sophisticated account not of its relevance, but of its necessity. ‘Postcoloniality is also, like most things, a matter of class’, he wrote with the kind of sharpness that defined his prose. In Theory taught an entire generation how to think about and write theory. In this book, and in essays published by Monthly Review, Aijaz mounted an important defence of the Marxist tradition. ‘Marx is boundless’, Samir Amin wrote, a line that Aijaz discussed with me when we produced a book of Samir’s later writings with a foreword from Aijaz. That boundlessness exists because the critique of capitalism is also incomplete until capitalism is overcome. To reject Marx, therefore, is to reject the most powerful set of tools that have been produced to explore the capitalist system and its grip on humanity. ‘Every country gets the fascism it deserves’, is a sentence that can be found in Aijaz’s writings from this period, when his reading of Gramsci helped to illuminate for him the rise of Hindutva in the period just before and after the destruction of the Babri Masjid in 1992. An entire generation in India, bewildered by the rapid acceleration of the twin phenomena of liberalisation and the growth of Hindutva, took refuge in Aijaz’s clear prose, which identified the character of the rise of the Indian hard right. His thoughts, many of them collected in Lineages of the Present: Political Essays (Tulika, 1996), described in precise theoretical and historical language the growth of the hard right. These considerations would never leave Aijaz. In the last decade of his life, he studied with great carefulness the oeuvre of the hard right. These readings became the Wellek Lectures, which he delivered at the University of California (Irvine) in 2017, and which will be collected and published by LeftWord Books. One of Aijaz’s contributions in his critiques was the way he insisted on the hard nature of Indian culture — rooted in the wretchedness of the caste system and the hierarchy of patriarchy. That’s what he meant in the aphorism about every country getting the fascism it deserves. To understand the roots of Hindutva, one had to grasp the taproot of hard culture, understand the way in which the privatisation agenda brutalised labour even more, and created the conditions for the rise of the political Hindu right. These writings, many of them delivered as lectures across India during a time of great political confusion, remain classics, necessary to read and re-read as we continue to face an assault on human dignity from these fascistic forces. Aijaz gave us confidence when the eclipse of hope seemed almost complete. Those were rough years. India liberalised in 1991. The United States opened up a cruel assault on Iraq in that same year. The next year, 1992, the forces of the hard right destroyed a sixteenth-century mosque in Ayodhya. Two years later, in 1994, the World Trade Organization was established. The resources of socialism were much depleted. During this decade, Aijaz’s writings and speeches — often published in small magazines and party publications — were widely circulated. In Delhi we had the good fortune to listen to him regularly, not only in public venues but at such places as Kutty’s tea house at the Nehru Memorial Museum and Library — where he was a Senior Fellow — and at the many Students’ Federation of India events that he attended as a speaker. In 1997, when Arundhati Roy published her novel The God of Small Things, Aijaz read it with great care and enthusiasm. I was at a meeting with N. Ram and Aijaz around that time, when they spoke of the book, and Ram asked Aijaz to write about it for Frontline. That essay — Reading Arundhati Roy Politically — is a gem of literary criticism and one that was, oddly, not anthologised in either Aijaz’s collections or in books on Arundhati’s work. The essay began a long relationship with Frontline that endured till the very end. Aijaz would write for it long articles to orient readers to the conjunctural events in the world, in particular the devastating turn of events after 9/11, the wars on Afghanistan and Iraq, the wars in Syria and Libya, and then the growth of the left in Latin America led by a man that we all admired, Hugo Chávez. These essays, once more circulated widely, became the basis for Aijaz’s book, Iraq, Afghanistan, and the Imperialism of Our Time (LeftWord, 2004). In the mid-1990s, after the fall of the USSR, it became evident that Marxism was suffering in the battle of ideas as neoliberalism entered not only the vocabulary of popular culture (with individualism and greed at the centre) but through postmodernism also entered the intellectual world. The lack of a serious left-wing publishing project dismayed us all. It was in this period, in 1999, that the publishing house LeftWord Books was set up in Delhi. Aijaz was one of its first authors, writing a sizzling essay on the Communist Manifesto in the book edited by Prakash Karat, A World to Win. Aijaz was on the publisher’s editorial board and encouraged us right through the past decades with the direction of our work. Towards the end of his life, Sudhanva Deshpande, Mala Hashmi and I spent some days with Aijaz to interview him at length about his life and his work. The interview was eventually published as Nothing Human is Alien to Me (LeftWord, 2020). During his last two years, Aijaz planned to write a series of introductions to Marx’s political writings. ‘Marx is thought of too narrowly for his economic work, which is important’, he would say, ‘but his political writings are key to understanding his revolutionary vision’. We did a series of interviews about some of these texts (Communist Manifesto, the first section of the German Ideology, The Eighteenth Brumaire, Marx’s writings on the Paris Commune), which we will convert into the introductions he imagined, as well as produce a collection of his writings on Marx. In 2009, Prabir Purkayastha and others started Newsclick, a web-based news portal to discuss the important issues of our times. Aijaz was one of its early guests and continued to be a regular voice on the Newsclick channel. He would explain with precise detail the wars in West Asia and North Africa as well as the political developments in the United States and China, South America and Europe. These conversations are an archive of those times. They also bring out Aijaz’s wit, his smile alerting one to a sharp comment. Between the Frontline columns and the Newsclick interviews, a generation of people learned not only about this or that event but also how to think of the world as a structured whole, how to understand events in relation to the great processes of our time. Each of these interventions was like a seminar, a gathering to learn how to think as much as to learn about what was happening. Aijaz taught at universities in India, Canada and the United States, and lectured at many institutions, from the Philippines to Mexico. Towards the end of his life, he became a Senior Fellow at Tricontinental: Institute for Social Research, where he advised a new generation of intellectuals on the boundlessness of Marxism. He was eager to spend some time on popular education, on building up the confidence of new intellectuals in our long-term battle of ideas. When a person such as Aijaz leaves us, his voice remains in our ears. It will be with us for a long time yet. * First published in Newsclick (India) on 10 March 2022, https://www.newsclick.in/life-great-marxist-aijaz-ahmad-1941-2022